Activity of The Resident Population in The North-East Region at the 2021 Census - Eugenia Harja; Oana Ancuța Stângaciu (Studies and Scientific Researches: Economics Edition)
The present paper starts from the analysis of the first definitive data on the resident and active population, published for the population census of December 1, 2021, both at the level of the North-East Region compared to the national level, and at the component counties. The evolution of the population and the labor force was analyzed with its main component, the employed population, both dynamically compared to the previous census, and in more detail according to different criteria for the situation existing on December 1, 2021. If the NE Region lost 2.29% of its resident population between the last two censuses, the active population decreased in a higher proportion (-19.08%), compared to the dynamics of the inactive population (+12.44%). This led to a decrease of the employed population by 21.95% (-316.4 thousand people). Agriculture remains the main activity of the region's population, representing 35.24% of this activity at the national level and 28% of the total employed population at the regional level. Although it is the largest region numerically, due to the lower degree of economic development of the area, a higher level of poverty, a lower offer of well-paid jobs, a significant part of the labor force tends to migrate to other places in the country or in other states, with consequences for the entire balance.